THE TECHNIQUE OF ZETA-COORDINATE DETERMINATION USING A TIME-DIFFERENCE MEASUREMENT FOR THE ZEUS CENTRAL TRACKING DETECTOR - Harnew, N; Nash, J; Salmon, G; Shield, P; Jeffs, M; Parham, A; White, D (1989)
A method to determine the z-coordinate of a track using a time-difference measurement has been developed for the ZEUS Central Tracking Detector. It has been demonstrated that a spatial resolution of 50 mm can be obtained under normal chamber operating conditions. This corresponds to a time-difference resolution of 330 ps. A method of minimizing nonlinearities in the time-to-distance response is described. This uses an inductor to form a matching network to achieve resistive termination of the chamber. Test beam measurements from a prototype chamber are presented, demonstrating the effects of the chamber surface field and beam incidence angle on the time-difference resolution.